2016
DOI: 10.1534/genetics.115.185843
|View full text |Cite
|
Sign up to set email alerts
|

Extra Microchromosomes Play Male Determination Role in Polyploid Gibel Carp

Abstract: Sex is generally determined by sex chromosomes in vertebrates, and sex chromosomes exhibit the most rapidly-evolving traits. Sex chromosome evolution has been revealed previously in numerous cases, but the association between sex chromosome origin and the reproduction mode transition from unisexual to sexual reproduction remains unclear. Here, we have isolated a male-specific sequence via analysis of amplified fragment length polymorphism from polyploid gibel carp (Carassius gibelio), a species that not only h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 59 publications
2
81
0
1
Order By: Relevance
“…Owing to its unique reproduction modes and polyploidy background, some allopolyploid clones or strains are able to be easily synthetized from different clones by incorporating an alien sperm genome (Gui & Zhou, ; Gui et al., a; Gui, Liang, Zhu, & Jiang, b; Li, Zhang et al. (); Li, Liang et al. (); Zhu & Gui, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its unique reproduction modes and polyploidy background, some allopolyploid clones or strains are able to be easily synthetized from different clones by incorporating an alien sperm genome (Gui & Zhou, ; Gui et al., a; Gui, Liang, Zhu, & Jiang, b; Li, Zhang et al. (); Li, Liang et al. (); Zhu & Gui, ).…”
Section: Discussionmentioning
confidence: 99%
“…Five of 70 allopolyploid individuals by ploidy determination were randomly selected to count chromosome number. The preparation of metaphase chromosomes was performed as described (Zhu & Gui, ; Li, Zhang et al., ). A total of the best 100 metaphase spreads were detected and the statistics modal number was characterized as the chromosome number (Li, Liang et al., ; Liu et al., ; Wang et al., ; Zhou & Gui, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AFLP analysis was conducted using a male‐specific primer pair (F: 5′‐TGT TGA GCG TGA TGT GAG TGA GC‐3′, R: 5′‐AAA CAA ACA CCA GGG CAG GAC TA‐3′) as per previous description (Pan et al., ). The PCR products were separated using 6% denaturing polyacrylamide gel (Bio‐Rad, Sequi‐Gen GT System) and visualized via silver staining (Li et al., ; Wang, Mao, Chen, Liu & Gui, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, unlike most unisexual vertebrates (Avise, 2008), gibel carp has been revealed to have multiple reproduction modes including unisexual gynogenesis and sexual reproduction (Zhou et al, 2000;Gui and Zhou, 2010;Li et al, 2014a;Mei and Gui, 2015;Zhang et al, 2015), and a high male incidence has been also observed in many natural populations (Jiang et al, 2013;Li et al, 2016). Utilizing it as an evolutional development biology model for screening reproduction-related genes, many important genes, such as oocytespecific and ovarian development-associated genes C-type lection (Dong et al, 2004), C1q-like (Mei et al, 2008(Mei et al, , 2014 and spindlin (Sun et al, 2010), oocyte-specific H2A variant h2af1o (Wu et al, 2009;Yue et al, 2013) and stem-loop binding protein-encoded gene slbp2 (Liu et al, 2015a), testis determination-related gene Dmrt1 (Li et al, 2014a), and germ cell marker genes Vasa and Dazl (Xu et al, 2005;Peng et al, 2009), have been identified and functionally characterized in gibel carp.…”
Section: Introductionmentioning
confidence: 99%